Changes in hair cortisol and oxytocin independently associate with positive and negative psychological states in female soccer players - Ohara, N.; Kameo, H.; Ochi, G. (Frontiers in Sports and Active Living, 2025)
Introduction: This study examined changes in hair cortisol concentration (HCC) and hair oxytocin concentration (HOC) in female athletes and aimed to clarify their relationships with training load, daily life stressors, and mental health indicators. Methods: Hair samples were collected from 22 female university soccer players (age: 19.8 ± 0.8 years), and psychological assessments were conducted in February and March 2024. Cortisol and oxytocin were extracted and measured from hair, and their associations with mood states [measured using the Profile of Mood States 2nd Edition (POMS2)], psychological distress [measured using the Kessler Psychological Distress Scale-6 (K6) scale], and self-reported training load were analyzed. Results: Training load and POMS fatigue levels increased significantly from February to March (t = 4.27, P < 0.001 and t = 4.74, P < 0.001, respectively); however, despite these increases in physical demands and perceived fatigue, no significant changes were observed in HCC and HOC. Regression analysis using M-estimation revealed that changes in academic stress were significantly negatively associated with HCC changes (ß = -1.04, p = 0.026), and changes in training load showed a positive association trend with HOC changes (ß = 0.0003, p = 0.068). Spearman correlation analysis showed a significant negative correlation between HCC changes and POMS vigor changes (rs = -0.44, p = 0.039) and a significant positive correlation between HOC changes and K6 scale changes (rs = 0.43, p = 0.043). No significant correlation was found between HCC and HOC. Discussion: HCC and HOC fluctuated independently and were associated with distinct psychological outcomes: HCC changes correlated with vigor, while HOC changes correlated with psychological distress. These findings suggest that each hormone may capture different dimensions of chronic stress and psychological functioning. Conclusion: Combined measurement of HCC and HOC may be useful in assessing chronic stress in female soccer players, providing complementary information for athlete health management.